1969
DOI: 10.1017/s002531540003719x
|View full text |Cite
|
Sign up to set email alerts
|

Larval nematodes in the herring (Clupea harengus) from British coastal waters and adjacent territories

Abstract: Investigations on larval nematodes in herring revealed that Anisakis sp. larvae occurred in the body cavity of 34 % of 5646 juvenile and adult herring examined; and that the infection increased with increase in fish length (age) and varied with the locality, being greater in herring caught nearer to the British coasts. The effect of temperature and salt concentrations on the survival of the larvae and the public health hazards of the larvae were discussed.Fifteen per cent of 3320 juvenile herring examined were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
1

Year Published

1976
1976
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 14 publications
3
40
1
1
Order By: Relevance
“…In the same way as decribed above the 4th larval stages were obtained in vitro by Grainger (1959), Khalil (1969), Koyama etal. (1969, Gibson (1970), Banning (1971), Schulz (1974), Sommerville (1974.…”
Section: Australian Blue Whiting ( Micromesistius Australis ) Theramentioning
confidence: 97%
See 1 more Smart Citation
“…In the same way as decribed above the 4th larval stages were obtained in vitro by Grainger (1959), Khalil (1969), Koyama etal. (1969, Gibson (1970), Banning (1971), Schulz (1974), Sommerville (1974.…”
Section: Australian Blue Whiting ( Micromesistius Australis ) Theramentioning
confidence: 97%
“…To stimulate moulting he supplied the medium with fresh fish flesh. Khalil (1969) used a commercially available ,,Medium 199" with a liver extract and horse serum. Gibson (1970) studied the development of the Anisakis larvae in rats experimentally infested through surgically grafting the larvae on the stomach wall.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by Grabda J. (1976) in case of the Baltic cod and by Khalil (1969) in case of spratt, Sprattus sprattus aged 1-4 from the North Sea. This author however,observed also a decrease of infesta tion with these larvae with the growth of studied herrings from the North Sea.…”
Section: Discussionmentioning
confidence: 58%
“…Grabda's (1976) studies showed, too that extensity of infesta 0 tion of the Baltic cod with these larvae increase distinctly when fish measured 70-75 centimetres. Data showing the increase of infestation with A. simplex with age of herring, Clupea harengus give Khalil (1969) and Grabda J. (1974).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in geographic distribution, prevalence and mean numbers of various parasites have been successfully used by several authors to distinguish between different stocks of host fish or as indicators of movements of specific fish stocks (Bishop & Margolis 1955, Sindermann 1957, 1961, Templeman & Squires 1960, Sherman & Wise 1961, Kabata 1963, Margolis 1963, Kilambi & Delacy 1967, Khalil 1969, Pippy 1969, Parsons & Hodder 1971, Davey 1972, Gibson 1972.…”
Section: Introductionmentioning
confidence: 99%